2014
DOI: 10.1016/j.solmat.2013.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanowire networks: Physical properties and potential integration in solar cells

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…The resistance of the AgNW intersections mainly depends on the contact areas between these wires. To reduce the resistance at the intersection, a heat treatment step [32,33] or an optical postprocessing step like plasmonic/UV welding [34] and pulsed laser sintering [35] can be carried out which yields an intimate contact of wires due to a local sintering of wires at their contact areas [32,36].…”
Section: Effects Of Thermal Treatment On the Electrical Resistivity Omentioning
confidence: 99%
“…The resistance of the AgNW intersections mainly depends on the contact areas between these wires. To reduce the resistance at the intersection, a heat treatment step [32,33] or an optical postprocessing step like plasmonic/UV welding [34] and pulsed laser sintering [35] can be carried out which yields an intimate contact of wires due to a local sintering of wires at their contact areas [32,36].…”
Section: Effects Of Thermal Treatment On the Electrical Resistivity Omentioning
confidence: 99%
“…1 It has even been shown that by further optimizing the deposition and post-deposition conditions, and the aspect ratio (length/diameter) of the nanowires, the resulting networks can surpass the electro-optical properties of (ITO). 9 AgNW networks have been investigated or even efficiently integrated into devices such as transparent heaters, [12][13][14][15] solar cells, [16][17][18][19][20] touch screens, 21,22 electromagnetic shielding 23 or antennas, 24 OLEDs, 25 in electrochromic devices, 26 for medical purposes 27 as well electrically conductive textiles 28 . Despite the attracting potentialities described here above, the integration of AgNW based TE in real devices is not yet widely considered in industrial devices due namely to their potential thermal 29 and electrical 30 instabilities, as well as low adhesion 7 and aging issues.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we visualize these changes in the network, both experimentally using passive voltage contrast electron microscopy techniques, 20 and in simulations of nanowires as line segments connected in a two-dimensional plane by junctions that can either be capacitive before activation or resistive after activation. 9,19,[21][22][23][24] We compare devices of different electrode geometry: two flat electrodes, one serrated and one flat electrode, two serrated electrodes, and one pointed and one flat electrode. By extending our previously developed model of connectivity in these networks, 2 we can predict the effects of microstructuring electrodes on the activation voltage and sheet resistance of networks, confirmed here through experimental data.…”
mentioning
confidence: 99%